2020
DOI: 10.3390/ijerph17176396
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of the Neighborhood Risk Factors for Respiratory Health in the Australian Capital Territory (ACT): Implications for Emergency Planning

Abstract: The Australian Capital Territory (ACT) experienced the worst air quality in the world for several consecutive days following the 2019–2020 Australian bushfires. With a focus on asthma and Chronic Obstructive Pulmonary Disease (COPD), this retrospective study examined the neighborhood-level risk factors for these diseases from 2011 to 2013, including household distance to hospital emergency departments (ED) and general practices (GP) and area-level socioeconomic disadvantage and demographic characteristics at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Other factors such as population size, distance to a hospital or response time of emergency services, and the residents' ability to be less reliant on primary health care providers to manage respiratory problems all appear to influence the number of presentations to a health care facility associated with wildfire smoke/atmospheric PM. 16,17 Climate predictions indicate wildfires will likely increase in frequency and severity and it is therefore imperative that EDs are adequately prepared for, briefed, and resourced to facilitate rapid mobilization of intervention teams following a disaster to minimize potential associated morbidity and mortality. 18 This literature review will therefore examine these challenges, together with the strategies for planning that have been implemented to best manage their effects.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors such as population size, distance to a hospital or response time of emergency services, and the residents' ability to be less reliant on primary health care providers to manage respiratory problems all appear to influence the number of presentations to a health care facility associated with wildfire smoke/atmospheric PM. 16,17 Climate predictions indicate wildfires will likely increase in frequency and severity and it is therefore imperative that EDs are adequately prepared for, briefed, and resourced to facilitate rapid mobilization of intervention teams following a disaster to minimize potential associated morbidity and mortality. 18 This literature review will therefore examine these challenges, together with the strategies for planning that have been implemented to best manage their effects.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology leverages Geographically Weigther Regression models (Fotheringham, Brunsdon, and Charlton, 2002) as they can identify spatially varying relationships, translated into a set of local regression outputs. These methods have been used recently in the field of health geography, and previous studies on asthma have demonstrated their suitability for studying the spatial behavior of their prevalence using a DH approach though scale-dependent effects and relationships -as the one we addressed -remain largely unexplored (Kumarihamy and Tripathi, 2019;Pala et al, 2019;Davies, Konings, and Lal, 2020).…”
Section: Methodsmentioning
confidence: 99%